Biointensive management of eggplant shoot and fruit borer, Leucinodes orbonalis - Gowda, B Hanumanthe; Ramesh, P R; Prashanth, J M (Indian Journal of Plant Protection, 2020)
Studies were conducted to assess the impact of the biointensive management (BIM) module through field demonstrations to manage brinjal shoot and fruit borer (BSFB), Leucinodes orbonalis in Tumkuru district of Karnataka. Results revealed that mean shoot infestation was 6.9% in demonstration fields compared to 29.8 % in check plots. Initially, the relative level of fruit damage between treated and untreated plot was not prominent. However, in later harvests the treatment effect became more evident. The average fruit infestation of 11.3% was recorded in BIM implemented plots, whereas check plots recorded the highest fruit infestation (31.4%) corresponding to higher yield (280.51q/ha) in demo than control plot (208.02 q/ha). Management of BSFB through this technology resulted in a benefit cost ratio of 2.48 to farmers